Peace, Security and the Development of Nigerian Communities - Adedokun, Mary O.; Bolarinwa, O. M. (NIU Journal of Social Sciences; Vol 5 No 4 (2019): KIU Journal of Social Sciences, Vol. 5 No. 4, December 2019, 2020)
A peaceful and secure environment is critical to every society because, it will affect all aspects of development economic, social and political. This work is predicated on the fact that when there is absence of peace and security, there can be no obvious development as efforts at development would always be truncated by absence of peace and insecurity. This research examines the issue of peace and security in Nigeria context and what its effects are on Nigerian communities. A descriptive research design of the survey type was used for the study. 164 respondents were used including people from various strata and occupations in communities in Ibadan, Oyo state capital and Ado-Ekiti, Ekiti State capital. The respondents included school children from age fifteen (15) to the tertiary level. The data collected were analyzed using Pearson’s Product Moment Correlation at 0.05 level of significance. The study found that unemployment, political insinuations, religious and land issues, ethnicity problems and unequal distribution of wealth are some of the causes of violence that lead to insecurity in Nigeria. Among others, it was recommended that governance should be more inclusive and participatory. Employment should be generated for all youth and the capacity of youth should be built to contribute to the building of more resilient, peaceful and secured community. The government at all levels should address the root causes of violence and ensure that everybody is free from fear so as to contribute to the development of their communities. Keywords: Peace, security, unemployment, development, good governance